Implementasi Teknologi Augmented Reality Sebagai Informasi Gedung 89 Teknik Elektro Fakultas Teknik Universitas Negeri Medan Berbasis Arduino - Dwi Waluyo, Bakti (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2024)
Augmented Reality (AR) can be utilized in various fields, one of which can be used as building information in an educational institution. The purpose of this research is to develop android-based media for building information using Augmented Reality technology with a marker-based tracking method. In developing this media, the MDLC method is used, and Unity with the Vuforia SDK is used. This research produces a building information media application, Augmented Reality technology to display information about rooms in a building that are suitable for use. This media makes it easier for users to recognize the function and location of rooms interactively by simply scanning markers. Thus, this technology provides a new and interesting experience while supporting the digitalization of information services in educational institutions.